Analisis Pengembangan Ruangan Terbuka Biru Pada Kawasan Wisata Waduk Lahor Di Kabupaten Malang Menggunakan Analytic Hierarchy Process (Ahp) - Adwinto Umbu Toku; Debora Budiyono; Dian Kartika Santoso (Universitas Trisakti, 2024)
Lahor Reservoir has great potential as an attractive tourist destination. With high natural and visual resources both natural and built landscapes this is an attraction for local and foreign tourists. In addition to the potential, the Lahor Reservoir tourist area also has weaknesses including some park facilities that are not well maintained, trash bins that are not well managed, circulation areas that are dirty due to leaves and branches, thus disturbing the quality of tidiness and cleanliness in the area. Based on this, the development of the Lahor Reservoir tourism area needs to be directed appropriately in order to provide maximum benefits. So, there needs to be an effort to improve and develop Blue Open Space at Lahor Reservoir by identifying and analyzing the tourism resources contained in Lahor Reservoir. The general method used in this research is descriptive quantitative and the analysis method used is Analytic Hierarchy Process (AHP) where this method focuses on solving a problem based on stakeholder preferences. The weight of the alternative assessment shows the priority of the Tourism alternative 0.496, the Reservoir Ecology alternative 0.215, the Socio-Cultural alternative 0.173 and the Economic alternative 0.116. From the assessment of these alternatives shows the best results in the development of Blue Open Space in the Lahor Reservoir tourism area that is sustainable is a Tourism-based model. The development of Blue Open Space in the Lahor Reservoir tourism area is divided into three development zones, namely the core zone, buffer zone and utilization zone. Zones that are less suitable for tourism development will be used as the core zone. Zones that are suitable enough for tourism development will be used as a buffer area.